Supervised Machine Learning Algorithms in Predicting Damaged Cargo: A Portuguese Logistics & Transportation Company Case Study - Vale, Alice Lourenço (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Business Analytics